Integrated assessment of water footprint in nonirrigated vineyards - Isabella Ghiglieno; Anna Simonetto; Luca Facciano; Manlio Migliorati; Marco Tonni; Pierluigi Donna; Marta Donna; Leonardo Valenti; Gianni Gilioli (Scientific Reports)
Abstract The topic of sustainable water management has become of paramount importance at a global level, especially when considering the high-amount of water used in agriculture, which is a threat to water resource balance. Focused on 38 inventories of nonirrigated vineyard management in the Franciacorta wine-growing region in Italy, this study aims to understand how agronomic practices impact water resources. The integrated statistical approach, based on generalized linear models, reveals how context variables influence different water footprint indicators, such as water scarcity, acidification and freshwater ecotoxicity. Plant density and the presence of hillside vineyards are the primary influencing factors, while others, such as variety susceptibility, vineyard age and soil type may influence the shortage of water. The outcomes help to better understand the impact of management, thereby raising awareness in the wine sector about aspects often overlooked in traditional investigations. These findings offer specific insights for viticulturists, emphasizing the importance of a tailored management approach to minimize water footprint in viticultural practices and contribute to environmental sustainability.